The environmental perspective on the impact of obsolescence of tank settlement (a case study of bulankulama tank, mihintale, sri lanka) - Wickramasinghe, W.M.P.W.; Gunarathne, G.S.P.; Senadheera, K.W.M.P. (University of Jaffna, 2018)
Wewa which used to name as Tank in Sri Lanka is considered as a symbol that exhibits the relationship between nature and human relationships. It is very clear offers a number of advantages only if it is in a viable condition. It is pity to imply that some tanks in Sri Lanka are going to obsolescence like Bulankulamatank, which is located in the Mihintale, North Central Province, Sri Lanka. This case study attempts to explore the environmental issues pertaining to the Bulankulama tank. The sample was 100 of households in the Mihintale GN division. Data were collected through a household survey using a structured questioner, key informant interviews,and field observation. The data were analyzed using descriptive statistical measures. The study found that the environmental issues of the tank were revealed as existing of invasive plants, water pollution, irregular solid waste dumping from various sources and reduction of aquatic flora and fauna.In addition, the prevailing environmental issues further aggravate the economic and social issues. Hence, Researchers strongly recommendminimizing the environmental issues in order to reduce the socio-economic impacts pertaining to the Bulankulama tank.
Keywords: Bulankulama tank; Environmental issues; Reasons; Socio-economic issues; Solutions